Fungal Endophyte: An Interactive Endosymbiont With the Capability of Modulating Host Physiology in Myriad Ways - Sarkar, Sohini; Dey, Abhijit; Kumar, Vinay; Batiha, Gaber El-Saber; El-Esawi, Mohamed A.; Tomczyk, Michał; Ray, Puja (Frontiers in Plant Science, 2021)
Endophytic fungi are a diverse group of non-pathogenic fungi which reside asymptomatically inside the tissue-spaces of plants and grow either intercellularly or intracellularly to complete whole or part of their life cycle in that host plant. They have been found to be associated with almost all the plants occurring in natural ecosystem. Due to their important role in the survival of plants they have been selected to co-evolve with their hosts through the course of evolution. Many years of intense research have discovered their tremendous roles in increasing the fitness of the plants in both normal and stressed conditions. There are numerous literatures regarding the involvement of various endophytic fungi in enhancing plant growth, nutrient uptake, stress tolerance etc. But, there are scant of reports documenting the specific mechanisms employed by fungal endophytes to manipulate plant physiology and exert their effects. In this review we aim to document the probable ways undertaken by endophytic fungi to alter different physiological parameters of their host plants. Our objective is to present an in depth elucidation about impact of fungal endophytes on plant physiology to make this evolutionarily conserved symbiotic interaction understandable from a broader perspective.